Return to work after coronary artery surgery for angina. Issue 6153 (16th December 1978) - Wallwork, J; Potter, B; Caves, P K
Abstract : The working habits of 115 consecutive patients who underwent coronary artery vein bypass grafting for angina were assessed. Only 25 patients worked up to the operation. Seven patients were housewives and seven retired. Sixty-eight patients had had to give up work because of their angina pectoris, and most of these had been off work for between six months and two years. After the operation 75 patients returned to full-time work, 59 within two to six months. These 75 patients included 23 of the 25 at work preoperatively and 47 of the 68 unable to work preoperatively. Most patients returned to their original occupation. We conclude that coronary artery surgery, as well as bringing symptomatic relief, increases the patient's ability to return to and maintain gainful employment.